ChemInform Abstract: A Bioinspired Synthesis of (.+‐.)‐Rubrobramide, (.+‐.)‐Flavipucine, and (.+‐.)‐Isoflavipucine. Issue 51 (5th December 2016) - Mizutani, Shoma; Komori, Kenta; Taniguchi, Tohru; Monde, Kenji; Kuramochi, Kouji; Tsubaki, Kazunori
Abstract: A biomimetic synthesis of racemic samples of the naturally occurring lactams rubrobramide (I), flavipucine (II), and isoflavipucine (III) is developed.